The Future of Andrew Marvell: Futurity in the Lyric Poems. - Tink, James (Critical Survey)
The modern reputation of Andrew Marvell has developed from studies of his status as a metaphysical poet of time and scale, to more historicist investigations of his political engagements and a nascent liberal subjectivity. There are remaining questions about the precise ideas of futurity in his lyric poetry. This article identifies three themes in particular: the figure of the child as part of a discourse of heredity, the figure of the landscape in a process of change, notably in 'Upon Appleton House', and the singularly charismatic figure of Oliver Cromwell, especially in 'An Horatian Ode'. It concludes by considering other potential notions of futurity as suggested through ecocriticism.